Pathways to behavior problems in Norwegian kindergarten children: The role of parent emotion socialization and child emotion understanding. Issue 6 (22nd June 2020) - Bjørk, Rune F.; Havighurst, Sophie S.; Pons, Francisco; Karevold, Evalill B.
Abstract : More than two decades of research have shown that parental emotion‐related socialization behaviors (ERSBs) significantly predict child emotion understanding and externalizing behavior problems. This study aimed to replicate these findings in a sample of 40 Norwegian preschool children and to test whether the effect of parental ERSBs on externalizing child behavior problems was mediated through child emotion understanding. Parental report on ERSBs was obtained using the Coping with Children's Negative Emotions Scale (CCNES) questionnaire. Child emotion understanding was assessed directly using the Test of Emotion Comprehension (TEC). The results showed that parental distress reactions and externalizing child behavior problems were significantly correlated and that parental expressive encouragement was significantly correlated with child emotion understanding. Estimation of indirect effects was conducted using process analysis and showed that parental expressive encouragement was indirectly related to externalizing child behavior problems ( b  = −0.17) via child emotion understanding. The results suggest that better child emotion understanding, and lower parental distress are related to lower levels of behavior problems in preschool children. These findings provide support for the Parental Meta‐Emotion Philosophy (PMEP) model, where the effect of parental emotion socialization on externalizing child behavior problems is mediated through emotion understanding.